Broader anti-EBV TCR repertoire in multiple sclerosis: disease specificity and treatment modulation - Schneider-Hohendorf, Tilman; Wünsch, Christian; Falk, Simon; Raposo, Catarina; Rubelt, Florian; Mirebrahim, Hamid; Asgharian, Hosseinali; Schlecht, Ulrich; Mattox, Daniel; Zhou, Wenyu; Dawin, Eva; Pawlitzki, Marc; et al. (Brain, 2025)
Epstein-Barr virus (EBV) infection has long been associated with the development of multiple sclerosis (MS). Patients with MS have elevated titres of EBV-specific antibodies in serum and show signs of CNS damage only after EBV infection. Regarding CD8+ T cells, an elevated but ineffective response to EBV was suggested in MS patients, who present with a broader MHC-I-restricted EBV-specific T-cell receptor beta chain (TRB) repertoire compared to controls. It is not known whether this altered EBV response could be subject to dynamic changes, e.g. by approved MS therapies, and whether it is specific for MS.Peripheral blood TRB repertoire samples (n = 1317) of healthy donors (n = 409), patients with MS (n = 710) before and after treatment, patients with neuromyelitis optica spectrum disorder (n = 87), MOG antibody-associated disease (MOGAD) (n = 64) and Susac’s syndrome (n = 47) were analysed.Apart from MS, none of the evaluated diseases presented with a broader anti-EBV TRB repertoire. In MS patients undergoing autologous haematopoietic stem-cell transplantation, EBV reactivation coincided with elevated MHC-I-restricted EBV-specific TRB sequence matches. Therapy with ocrelizumab, teriflunomide or dimethyl fumarate reduced EBV-specific, but not CMV-specific MHC-I-restricted TRB sequence matches.Together, these data suggest that the aberrant MHC-I-restricted T-cell response directed against EBV is specific to MS with regard to neuromyelitis optica, MOGAD and Susac’s syndrome and that it is specifically modified by MS treatments interfering with EBV host cells or activated lymphocytes.
Veröffentlicht: 18. Juli 2024
Gesehen am 10.06.2025